2020
DOI: 10.3390/biom10040629
|View full text |Cite
|
Sign up to set email alerts
|

AAA+ ATPases in Protein Degradation: Structures, Functions and Mechanisms

Abstract: Adenosine triphosphatases (ATPases) associated with a variety of cellular activities (AAA+), the hexameric ring-shaped motor complexes located in all ATP-driven proteolytic machines, are involved in many cellular processes. Powered by cycles of ATP binding and hydrolysis, conformational changes in AAA+ ATPases can generate mechanical work that unfolds a substrate protein inside the central axial channel of ATPase ring for degradation. Three-dimensional visualizations of several AAA+ ATPase complexes in the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 170 publications
(322 reference statements)
2
34
0
Order By: Relevance
“…Breaking such interpretive limits or reducing inference ambiguity might require more structural snapshots along the path of conformational changes. For instance, the seven cryo-EM structures of the substrate-bound human 26S proteasome obtained under a common buffer condition contain inherent features of ubiquitin and substrate densities verifying the time sequence of the corresponding states along the path of chemical reactions (Table 1.2) (Dong et al 2019;Zhang and Mao 2020). These structures establish themselves as a spatiotemporal continuum and provide direct evidence for sequential ATP hydrolysis around the proteasomal ATPase ring with a mixture of Modes 1, 2 and 3 (Dong et al 2019).…”
Section: Coordinated Atp Hydrolysis Around the Atpase Ringmentioning
confidence: 93%
See 1 more Smart Citation
“…Breaking such interpretive limits or reducing inference ambiguity might require more structural snapshots along the path of conformational changes. For instance, the seven cryo-EM structures of the substrate-bound human 26S proteasome obtained under a common buffer condition contain inherent features of ubiquitin and substrate densities verifying the time sequence of the corresponding states along the path of chemical reactions (Table 1.2) (Dong et al 2019;Zhang and Mao 2020). These structures establish themselves as a spatiotemporal continuum and provide direct evidence for sequential ATP hydrolysis around the proteasomal ATPase ring with a mixture of Modes 1, 2 and 3 (Dong et al 2019).…”
Section: Coordinated Atp Hydrolysis Around the Atpase Ringmentioning
confidence: 93%
“…The AAA domain of RPT contains highly conserved motifs commonly observed in the AAA+ superfamily proteins, including Walker A, Walker B, inter-subunit signaling (ISS) motif, sensor 1, arginine finger (R-finger), sensor 2, and pore-1/2 loops (Fig. 1.21) (Sauer and Baker 2011;Ogura and Wilkinson 2001;Lupas and Martin 2002;Iyer et al 2004;Hanson and Whiteheart 2005;Erzberger and Berger 2006;Chang et al 2017;Zhang and Mao 2020;Puchades et al 2020). The nucleotidebinding pocket is intimately surrounded in "cis" by Walker A, Walker B, sensor 1, and sensor 2 within the same AAA domain, and two R-fingers and ISS motif in "trans" from the large AAA subdomain of the clockwise adjacent ATPase subunit (Wendler et al 2012).…”
Section: Proteasomal Aaa-atpase Motormentioning
confidence: 99%
“…Early crystallographic and EM structures of ASCE ATPases without their polymeric substrates bound indicated that most were assembled as planar hexameric rings. More recently, several structures of ASCE ATPases complexed with their polymeric substrates have been determined to near-atomic resolution by single particle cryoEM (53). Many of these structures have a helical arrangement of subunits rather than a planar-ring organization.…”
Section: Structural Comparison Of the Phi29 Packaging Motor And Othermentioning
confidence: 99%
“…The mechano-chemical cycle begins when all five ATPase subunits have bound ATP at the end of the dwell. As with many ASCE ATPases, gp16 has a high affinity for DNA when ATP is bound and lower affinities in ADP-bound and apo states (53,58). To optimally engage its DNA substrate, the NTD adopts a helical arrangement that is approximately complementary to the DNA.…”
Section: Mechanism Of Translocationmentioning
confidence: 99%
“…AAA-ATPases serve as proteolytic motors, allowing the recruitment and unfolding of substrates carrying specific degradation signals [96,97]. Typically, they form hexameric rings, where the proteolytic subunits assemble into a cylinder-shaped structure, with a pore at the central axis, forming the catalytic chamber.…”
Section: The Molecular Mechanism Of Cdc48/p97mentioning
confidence: 99%